Psychological Counselling and Counselling Psychology: development path, current state and trends - Khachatryan, Narine (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article presents the counselling psychology as an applied field and specialty in psychology. A brief overview of the formation of counselling psychology as a specialty in US, United Kingdom, Canada and Australia is given, as well as the challenges and trends of the development of counselling psychology are determined. Special attention is given to phylosophical base, identity and methodology of counselling psychology as a special, separate field in psychology. At the end of the article the challenges and trends of development of counselling psychology in Armenia are outlined.